Taxonomy and phylogenetics of Malaysian sargassum species (Fucales, Phaeophyceae) / Ng Woan Shien - Ng, Woan Shien (2013)
Sargassum is one of the most diverse and complex genera in Phaeophyceae.Morphological plasticity of this genus has always resulted in difficulty in Sargassum species delineation. Malaysia as one of the hotspots recorded for Sargassum diversity has an available checklist record of 34 taxa. The existing classification of Malaysian Sargassum is based mainly on morphological characters. None has yet been revised using molecular data. The aim of this study is to use a combination of morphological and molecular data to resolve some taxonomy confusion and produce a more comprehensive phylogeny for the current species found in Malaysia. A survey was conducted throughout Malaysia and over 850 Sargassum specimens were newly collected and deposited in the Seaweeds and Seagrasses Herbarium, University of Malaya (KLU). 22 taxa from the Herbarium were revised morphologically whereby 14 newly collected taxa were subjected to DNA analyses in present study. Specimens were sequenced using the nuclear ITS-2, plastid partial Rubisco operon and mitochondrial cox3 markers. The identification of the fourteen species distinguished in this study using both morphology and DNA sequence analyses was confirmed by the examination of original diagnoses and type specimens when possible. One taxon remained unidentified.Descriptions of the fourteen taxa’s morphological variability were provided as well as an identification key for their identification. The phylogeny of Malaysian Sargassum was constructed using concatenated dataset. Only taxa from Sargassum subgenus Sargassum was found in Malaysia and represented in the sections Binderiana, Ilicifolia and Polycystae. The phylogeny was highly resolved at the sectional level and confirmed the current proposed revision within the genus. This study is the first comprehensive phylogenetic analysis of Malaysian Sargassum using three molecular markers. Apart iii from that, the status of several species also been reconsidered. Firstly, Sargassum siliquosum which was previously placed in section Malacocarpicae has been moved into section Ilicifolia. Secondly, the synonymy of Sargassum binderi and Sargassum oligocystum was confirmed with molecular evidence from both type specimens. Thirdly, the sequences of Sargassum binderi, Sargassum oligocystum, Sargassum polycystum and Sargassum stolonifolium from type localities are provided for the first time for phylogenetic analyses. Lastly, four new records (Sargassum densicystum, Sargassum longifructum, Sargassum marginatum and Sargassum cf. parvifolium) are reported in this thesis.